2010
DOI: 10.1111/j.1600-0560.2010.01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Fas-ligand staining in non-drug- and drug-induced maculopapular rashes

Abstract: There is a trend toward Fas-L being more prevalent in the epidermis of drug maculopapular rashes, although this did not reach statistical significance. This is possibly because of the small sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Dermal eosinophilic infiltrate was also found in significantly higher number of drug (62.5%) as compared with viral exanthem biopsies ( 16.6 % cases). Wang et al found significant number of eosinophils in only 2 (20%) of 10 viral exanthem specimens and in 6 (60%) drug exanthem cases . Naim et al, Bellini et al, Gerson et al and Ortonne et al observed eosinophilia in 60%, 36.1 %, 50% and 45%, respectively, of their drug exanthem biopsies (Table ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Dermal eosinophilic infiltrate was also found in significantly higher number of drug (62.5%) as compared with viral exanthem biopsies ( 16.6 % cases). Wang et al found significant number of eosinophils in only 2 (20%) of 10 viral exanthem specimens and in 6 (60%) drug exanthem cases . Naim et al, Bellini et al, Gerson et al and Ortonne et al observed eosinophilia in 60%, 36.1 %, 50% and 45%, respectively, of their drug exanthem biopsies (Table ).…”
Section: Discussionmentioning
confidence: 96%
“…Stur et al in their study found increased levels of soluble FAS ligand (FAS‐L) in serum and biopsy specimens of drug‐induced exanthem cases compared with viral exanthem . Similarly, Wang et al found positive FAS‐L staining in 50% drug exanthem and only 10% of viral exanthem cases . Yawalkar et al found significantly higher number of IL‐5 and eotaxin‐positive cells in drug‐induced MPEs compared with psoriatic skin specimens, suggesting that these could be explored further to differentiate between drug and viral exanthems …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the primary electron microscopic changes of DIEs (intercellular and intracellular edema and disruption of epidermal basal cells with some pyknotic nuclei) observed by Fellner and Prutkin 18 in 4 patients with morbilliform eruption due to penicillin are present also in infectious exanthems. According to our results, the currently emphasized presence of eosinophils in the skin of drug eruptions is not specific because it is only more frequent (Table 2) and perhaps more marked 17 in DIEs than in VBIEs. In conclusion, there is not a single histopathologic feature that reliably differentiates a DIE from a VBIE (Fig.…”
Section: Discussionmentioning
confidence: 47%
“…The hydropic degeneration of keratinocytes at the basal layer (the so-called vacuolar interface dermatitis) and small foci of spongiosis in the lower epidermis have been considered the 2 most typical histopathologic features of DIEs. 14Y16 Nevertheless, these alterations are not a constant finding and are not diagnostic because they were seen in 30.5% and 40% of VBIEs investigated by us and Wang et al, 17 respectively. It is possible that the primary electron microscopic changes of DIEs (intercellular and intracellular edema and disruption of epidermal basal cells with some pyknotic nuclei) observed by Fellner and Prutkin 18 in 4 patients with morbilliform eruption due to penicillin are present also in infectious exanthems.…”
Section: Discussionmentioning
confidence: 92%
“…47,48 Ainda assim a biópsia pode ser útil na distinção de uma causa vírica ou auto-imune e estão a ser estudados novos marcadores imuno-histoquímicos -Fas-L, IL-5, perforina e granzina B -que poderão ajudar na identificação dos casos de exantema maculopapular induzidos por fármacos. 47,49 O diagnóstico etiológico, além da história clínica, pode ser complementado com testes cutâneos realizados após a resolução da toxidermia (testes epicutâneos ou intradérmi-cos de leitura retardada -para as reações de hipersensibilidade tipo IV -ou testes intradérmicos ou prick de leitura imediata -no caso das reações de hipersensibilidade tipo I) ou até testes de provocação nas toxidermias menos graves. 4,9,45,46 Os testes in vitro, alguns dos quais passíveis de ser realizados na fase aguda da toxidermia, incluem a pesquisa de IgE específica do fármaco nas reações imediatas, e estão a ser validados meios de diagnóstico in vitro como o teste de transformação ou ativação de linfócitos ou de produção de citocinas (ELISPOT) nas formas de toxidermias retardadas.…”
Section: Diagnóstico E Tratamento De Toxidermiasunclassified